Conduction characteristics in the left atrium of patients with perimitral atrial tachycardia post–pulmonary vein isolation - Mitsuru Takami, MD, PhD; Ryudo Fujiwara, MD, PhD; Atsushi Suzuki, MD, PhD; Kunihiko Kiuchi, MD, PhD; Kimitake Imamura, MD, PhD; Kenichi Tani, MD; Hidehiro Iwai, MD; Yusuke Nakanishi, MD; Mitsuhiko Shoda, MD; Atsushi Murakami, MD; Shogo Yonehara, MD; Mari Yamamoto, MD; et al. (Heart Rhythm O2)
Background: The electrical conduction properties of the left atrium (LA) in patients with perimitral atrial tachycardia (PMAT) after pulmonary vein isolation (PVI) are not completely understood. Objectives: The purpose of this study was to investigate the characteristics of the segmental conduction velocity (CV) in the LA using multisite pacing in patients with PMAT. Methods: After PVI in 179 patients, LA anterograde and retrograde propagation maps were created via pacing at different sites. Segmental CVs were measured in 7 distinct segments of the LA in both maps. Burst pacing was performed to induce atrial tachyarrhythmias. Results: Twelve PMATs (7 clockwise rotation, 5 counterclockwise rotation) were induced in 11 patients (PMAT group), whereas no atrial tachyarrhythmias were induced in 56 (no induction group). Comparing the segmental CVs between the PMAT and no induction groups, we observed significant reductions in the PMAT group CVs, not only in the anterior and septal regions but also in the roof and bottom regions. Direction-dependent conduction delays were also observed in regions without or with small low-voltage areas, especially in the LA septum, lateral, and bottom. In the PMAT group, the very slow conduction area during PMAT consistently matched the region of the most reduced CV during either anterograde or retrograde propagation. Additionally, the direction of greater conduction delays in the anterior LA identified during pacing studies matched the direction of the PMAT rotation in 9 of 11 patients. Conclusion: Patients with PMAT showed distinct segmental CVs in the LA, which may influence the tachycardia circuit formation and rotational direction.